Richard Bean’s The Big Fellah (2010) and Jez Butterworth’s The Ferryman (2017): two plays about the Northern Troubles from outside of Northern Ireland - Hiroko Mikami (Ilha do Desterro)
During the three decades of the Troubles of Northern Ireland (1969-1998), a remarkable amount of plays about the Troubles was written and almost of them, it seems, had been ‘monopolised’ by (Northern) Irish playwrights. Recently, however, certain changes about this monopoly have been witnessed and those who do not claim themselves as Irish descendants have begun to choose the Northern Troubles as their themes. Also, there have been growing concerns about violence worldwide since 9.11. This article deals with two plays, Richard Bean’s The Big Fellah and Jez Butterworth’s The Ferryman, neither of which was written by an Irish playwright and examines whether and to what extent it is possible to say that they can transcend regional boundaries and become part of global memories in the context of the post-Good Friday Agreement and the post 9.11.